Techniques for ESP Students in Teaching English - Fatmawati Fatmawati; Sofyan A. Gani; Iskandar Abdul Samad (Universitas Syiah Kuala, 2018)
The purposes of this study are to find out the lecturers’ technique in teaching English to Information Technology and Computer, describe the lecturers’ material development, and the way of assessing to Information Technology and Computer students at State Polytechnic of Lhokseumawe. This is a descriptive qualitative study. Two English lecturers at the Information Technology and Computer Department were selected as the participants in this study. Instruments were employed by the researcher to obtain the real data. Observation, interview and documentation were used as the instruments of data collection.The data were analyzed by using descriptive analysis. The results show that varieties of strategies were used by the lecturers in teaching English including communicative language teaching, Contextual Teaching Learning, Problem Based Learning and Learner Centered Approach. The lecturers modified the strategies in the teaching depended on the materials, such as applied the discussion model and used the video as media in teaching. Then, they connected the strategies with students’ experience; prior knowledge as well as the context of Polytechnic students such as the development of computer technology or others technology. The materials were developed by the lecturers to motivate students in learning English by referring to the syllabus and lesson Plan. The materials were developed from books, magazines, newspapers and internet, that involving four language skills: listening, reading, speaking and writing to suit the students’ need of State Polytechnic of Lhokseumawe. Both written and oral test were used by the lecturers for evaluating the learning achievement as a formal assessment. The continuous assessment type was applied as the lecturers’ way assessment to assess the Information Technology and Computer students. The students were not only given score but also feedback continuously.